Pengaruh Disiplin Kerja Dan Motivasi Kerja Terhadap Produktivitas Karyawan Pada PT Dos Ni Roha Logistic Jakarta - Ezral Yohanes Soedira (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2023)
PT Dos Ni Roha Logistic is a branch of DNR Corporation which has a function to fulfill the delivery of goods or pharmaceutical equipment by providing transportation services for the delivery of goods both land, sea and air. Data collection methods in this thesis research are questionnaires, observations, literature studies with a population of 47 employees and a sample of 47 determined using saturated sampling techniques and processed using SPSS software version 25. Work Discipline and Work Motivation together have a positive and significant influence on employee productivity Pt Dos Ni Roha Logistic Jakarta, Work Discipline and Work Motivation are one of the important factors that affect employee productivity, an employee if he has a level of work discipline and is given good motivation in Work can result in high levels of productivity. The results of this study show that work discipline and work motivation have a positive and significant effect on employee productivity, which is 0.546 or 54.6%, so it can be concluded that the influence on employee productivity is 0.546 or 54.6%, while the remaining 45.4% is influenced by other variables outside this study. Companies should need to improve work discipline and work motivation within the company in order to further increase the productivity of their employees.